Varying Dietary Component Ratios and Lingonberry Supplementation May Affect the Hippocampal Structure of ApoE–/– Mice - Shepilov, Dmytro; Kovalenko, Tatiana; Osadchenko, Iryna; Smozhanyk, Kateryna; Marungruang, Nittaya; Ushakova, Galyna; Muraviova, Diana; Hållenius, Frida; Prykhodko, Olena; Skibo, Galyna (Frontiers in Nutrition, 2022)
Objective: This study aimed to investigate and compare the morphological and biochemical characteristics of the hippocampus and the spatial memory of young adult ApoE-/- mice on a standard chow diet, a low-fat diet (LFD), a high-fat diet (HFD), and an HFD supplemented with lingonberries. Methods: Eight-week-old ApoE-/- males were divided into five groups fed standard chow (Control), an LFD (LF), an HFD (HF), and an HFD supplemented with whole lingonberries (HF+WhLB) or the insoluble fraction of lingonberries (HF+InsLB) for 8 weeks. The hippocampal cellular structure was evaluated using light microscopy and immunohistochemistry; biochemical analysis and T-maze test were also performed. Structural synaptic plasticity was assessed using electron microscopy. Results: ApoE-/- mice fed an LFD expressed a reduction in the number of intact CA1 pyramidal neurons compared with HF+InsLB animals and the 1.6-3.8-fold higher density of hyperchromic (damaged) hippocampal neurons relative to other groups. The LF group had also morphological and biochemical indications of astrogliosis. Meanwhile, both LFD- and HFD-fed mice demonstrated moderate microglial activation and a decline in synaptic density. The consumption of lingonberry supplements significantly reduced the microglia cell area, elevated the total number of synapses and multiple synapses, and increased postsynaptic density length in the hippocampus of ApoE-/- mice, as compared to an LFD and an HFD without lingonberries. Conclusion: Our results suggest that, in contrast to the inclusion of fats in a diet, increased starch amount (an LFD) and reduction of dietary fiber (an LFD/HFD) might be unfavorable for the hippocampal structure of young adult (16-week-old) male ApoE-/- mice. Lingonberries and their insoluble fraction seem to provide a neuroprotective effect on altered synaptic plasticity in ApoE-/- animals. Observed morphological changes in the hippocampus did not result in notable spatial memory decline.